2020
DOI: 10.1101/2020.12.04.412296
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cardiac metabolic imaging using hyperpolarized [1-13C]lactate as a substrate

Abstract: Hyperpolarized [1-13C]lactate is an attractive alternative to [1-13C]pyruvate as a substrate to investigate cardiac metabolism in vivo; it can be administered safely at a higher dose and can be polarized to a similar degree as pyruvate via dynamic nuclear polarization. While 13C cardiac experiments using HP lactate have been performed in small animal models, it has not been demonstrated in large animal models or humans. Utilizing the same hardware and data acquisition methods used in the first human HP 13C car… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This potentially has an impact on all hyperpolarized 13 C-pyruvate studies, as it implies that the 13 C-lactate observed can be coming from blood pool metabolic conversion instead of the tissue of interest. This circulating 13 C-lactate could also be a source of contrast as it can be used as a fuel source [ 30 32 ]. It will also introduce partial volume errors in voxels containing myocardium and blood pool, originating from the chambers and potentially coronary arteries, where the additional blood lactate would likely increase the 13 C-lactate/pyruvate and k PL .…”
Section: Discussionmentioning
confidence: 99%
“…This potentially has an impact on all hyperpolarized 13 C-pyruvate studies, as it implies that the 13 C-lactate observed can be coming from blood pool metabolic conversion instead of the tissue of interest. This circulating 13 C-lactate could also be a source of contrast as it can be used as a fuel source [ 30 32 ]. It will also introduce partial volume errors in voxels containing myocardium and blood pool, originating from the chambers and potentially coronary arteries, where the additional blood lactate would likely increase the 13 C-lactate/pyruvate and k PL .…”
Section: Discussionmentioning
confidence: 99%
“…This potentially has an impact on all hyperpolarized 13 C-pyruvate studies, as it implies that the 13 C-lactate observed can be coming from blood pool metabolic conversion instead of the tissue of interest. This circulating 13 C-lactate could also be a source of contrast as it can be used as a fuel source [30][31][32] . It will also introduce partial volume errors in voxels containing myocardium and blood pool, originating from the chambers and potentially coronary arteries, where the additional blood lactate would likely increase the 13 Clactate/pyruvate and k PL .…”
Section: Discussionmentioning
confidence: 99%